2021
DOI: 10.3126/janr.v4i2.33657
|View full text |Cite
|
Sign up to set email alerts
|

Prospect and potentiality of finger millet in Nepal: Nutritional security and trade perspective

Abstract: Millet is an important food crop for ensuring food and nutrition security of smallholder farmers and marginalized communities in the hill and mountain of Nepal. The main objectives of the study were to assess prospects and potentiality of millet by analysing the area, production, productivity, and trade for the year 2009-2019.  The study used a combination of exploratory survey and secondary data for assessing the production system, compound growth rate, coefficient of variation (CV), instability index (IIN), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The area under millet cultivation is decreasing because of shift of farmers towards the production of major cereals like rice, wheat, and maize. Finger millet possesses several beneficial characters like high photosynthetic efficiency, nutrient-dense, locally available, and climate resilience with high adaptation to drought and other biotic and abiotic stresses (Gairhe, Gauchan & Timsina, 2021).…”
Section: Production and Trade Scenario Of Millet In Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…The area under millet cultivation is decreasing because of shift of farmers towards the production of major cereals like rice, wheat, and maize. Finger millet possesses several beneficial characters like high photosynthetic efficiency, nutrient-dense, locally available, and climate resilience with high adaptation to drought and other biotic and abiotic stresses (Gairhe, Gauchan & Timsina, 2021).…”
Section: Production and Trade Scenario Of Millet In Nepalmentioning
confidence: 99%
“…finger millet import in Nepal and major portion of import goes in liquor production without any linkage in the domestic value chain(Gauchan, Bhandari, Gurung, Joshi & Jarvis, 2019). Study conducted byGairhe, Gauchan and Timsina (2021) revealed that millet import value and millet production in Nepal are rising at the rate of 14.62% and 0.47 % per year respectively. Higher2013/14 2014/15 2015/16 2016/17 2017/18 2018/19 2019/20 2020/21…”
mentioning
confidence: 99%
“…A simple analytical technique such as the coefficient of variation was used to measure the variance in any time-series data (Gairhe et al, 2018;Gairhe et al, 2021). It is estimated as follows: CV= (Standard deviation /Mean) *100…”
Section: Coefficient Of Variationmentioning
confidence: 99%
“…The TSI was used to assess the lentil's competitive status in Nepal. A group researchers used TSI to determine the competitiveness of millet in Nepal (Gairhe et al, 2021). The formula used is as follows: The value of this index ranges between -1 to +1.…”
Section: Trade Specialization Index (Tsi)mentioning
confidence: 99%
See 1 more Smart Citation